Defining, conceptualizing, and measuring gender violence across the world (2018)
While there still remains a gap in the literature on how to define, conceptualize, and measure gender violence cross-nationally, solving this challenge stands as the main objective of this research. Despite the lack of consensus regarding the definition of gender violence, in this chapterwe aim to elucidate the meaning of gender violence to provide an overall understanding of the concept. We suggest a new conceptualization of gender violence by focusing on 16 types of violence from a matrix of three dimensions and, as a result, we present a gender violence index that measures the prevalence and incidence of gender violence by using crosscountry data from the WomanStats database. The conceptualization provided by this study represents the basis for a measurement to determine the gap between different countries regarding the commonness of circumstances that could lead to gender violence. © 2018 by Nova Science Publishers, Inc. All rights reserved.